January 27, 2023

# Simplification questions for class 7 PDF

Different types of questions on simplifications are explained here step by step.

Contents

# Simplification questions for class 7(Solved examples)

(i)16+8 ÷ 4-2 x  3

Sol.  According to the     rule  we have to perform division first followed by  multiplication , addition and subtraction.

16+8 ÷ 4-2 x  3 =16+2-2 x  3                    ( performing division)

=16+2-6                              (performing multiplication)

= 12

(ii)

Sol. First we have to remove vinculum (bar) , this implies

(removing small brackets)

(removing curly braces)

= 23-23                                                            (removing big brackets)

=0

(iii)

Sol.                (removing bar)

=                                (removing small brackets)

(removing curly braces)

=25-4                                                            (performing multiplication)

=21

(iv) [(-10 x (25-)) ÷ (-5)]

Sol. [(-10 x (25-)) ÷ (-5)]= [(-10 x (25-10)) ÷ (-5)]                         (removing vinculum)

= [(-10 x (15)) ÷ (-5)]

=[(-150) ÷ (-5)]                                       (removing small brackets)

=      x 30                                                      (removing big brackets)

=  4+6                                                                       (performing  multiplication)

=10

(v) 8 − [28 ÷ {34 − (36 − 18 ÷ 9 × 8)}]

Sol. 8 − [28 ÷ {34 − (36 − 18 ÷ 9 × 8)}] =  8  [28 ÷ {34  (36 2 ×  8)}]              [solving division]
=     8  [28 ÷ {34  (36 −16)}]                    [Performing multiplication]
= 8  [28 ÷ {34 20}]                                    [Removing parentheses]
= 8 [28 ÷ 14]                                                [Removing braces]
= 8 2                                                              [Removing square brackets]

=6

(vi) 16  2 ÷ 7 + 6 × 2

Sol. 16  2 ÷ 7 + 6 × 2=

=

=

=

=

(vii) 197 – [{42 + (56 – )} +108]

Sol.   197 – [ {42 + (56 – )} +108] = 197 – [ {42 + (56 – 17)} + 108]       [Removing vinculum]

= 197 – [ {42 + 39} + 108]                [removing innermost brackets]

= 197 – [()+ 108]                          [Removing braces]

= 197 – [9 + 108]                                    [removing big brackets]

= 197 – 117

= 80

Students can practice these examples on simplification which are discussed here step by step and then proceed to the worksheet for more practice.

• ## Simplification questions for class 7  ( Unsolved questions with answers)

(i) 36-2(20+12÷ 4 x 3 -2 x 2)+10

(ii) 18+(28-7) ÷ 3 -11

(iii) { ÷}

(iv) {-5-(-48) ÷ (-16)}

(v) ÷ ÷

(vi) ÷

(vii)  8-[28÷{34-(36-18÷9 x 8)}]

(viii)

(ix) ÷

(x)  54 ÷3 of 6+9

(xi)19  [4 + {16  (12  2)}]

(xii) 36  [18  {14  (15  4 ÷2 ×2)}]

(xiii) 39 – [23 – {29 – (17 – )}]

(xiv) 15 – (-5) {4 – } ÷ [3{5 + (-3) x (-6)}]

Ans. (i)  -4       (ii) 14    (iii)      (iv) 24    (v) 4     (vi)       (vii)  6    (viii)            (ix) 3      (x) 12    (xi) 9     (xii) 21      (xiii)34     (xiv) 15

### Bodmas questions for class 7 worksheet 